Transitioning from methadone to buprenorphine maintenance in management of opioid use disorder during pregnancy. (4th May 2018) - Johnson, Shakevia; Martin, Peter R.
ABSTRACT: Background : Opioid use disorder during pregnancy is a growing health concern. Methadone maintenance is the treatment of choice but emerging data indicate buprenorphine is a viable alternative. Due to costs and limited accessibility of methadone, pregnant women may require transition from methadone to buprenorphine for maintenance treatment. Objectives : To assess safety and effectiveness of transitioning from methadone to buprenorphine when necessary during pregnancy. Methods : A standardized protocol using low buprenorphine doses to minimize emergent withdrawal symptoms under careful obstetric and psychiatric monitoring was implemented in 20 pregnant women. Outpatient maternal and neonatal outcomes were assessed. Results : Women maintained on an average methadone dose of 44 ± 4.77 (20–100) mg/day (mean±standard error mean (SEM); range) were successfully transitioned to 12.60 ± 0.8 (8–16) mg/day (mean±SEM; range) of buprenorphine. Within 4 weeks of transition, 15% had illicit drugs detected in urine drug screens. Ninety percent of women maintained outpatient follow-up until delivery. At delivery, 38.9% of mothers were exclusively adherent to buprenorphine (without use of illicit substances and/or other psychotropic medications); this resulted in significantly lower rates of neonatal abstinence syndrome (NAS) and shorter hospital stays. Discussion : Pregnant women transitioned from methadone to buprenorphine maintenance showed maternal and neonatal outcomes comparable to studies of women on buprenorphine throughout pregnancy. Infants born to buprenorphine-maintained women who abstained from illicit substances and other prescribed psychotropic medications experienced less severe NAS and shorter hospitalizations compared with women with illicit substance use and other psychotropic medications. These findings suggest women can safely be transitioned from methadone to buprenorphine during pregnancy.